RELASI GENDER PADA RUMAH TANGGA PETANI PADI SAWAH DI KECAMATAN MILA KABUPATEN PIDIE - Elly Susanti; Agus Sabti; Nisa Farhani (Universitas Teuku Umar, 2016)
This study aims to look at the role of husband and wife in terms of division of labor and time spent on productive activities, reproductive and social community on domestic rice farmers in the district of Mila and also to be able to know how access to factors of production, control the husband and wife on productive activity, reproductive and social community on domestic rice farmers in the district of Pidie district Mila. Gender relations can be determined by looking at the ratio of response of husband and wife, as well as the amount of time spent in each activity. The study was conducted in the village of Pulo Tanjong Mila districts by considering that the greater part of people both men and women farmers. The discussion outlined using a quantitative approach to perform tabulations on the results of respondents' answers will then be described to explain the data obtained in the field. The results showed the division of labor and spent of the time on more productive activities performed by the husband (113 hours) and wife (105 hours), the wife of reproductive activities dominate (10.28 hours) while the husband (2.82 hours), social activities community with almost the same number of division of labor and complementarity, husband (8.35 hours) and wife (7.46 hours). Husband had access to factors of production greater than the wife. In terms of controls on the husband's decision also have more control grows in farming, while the reproductive and social activities wife would dominate decision making.